Terapi Musik dalam Menurunkan Kecemasan Remaja di Masa Pandemi Covid-19 - Sulistyorini Sulistyorini; Siti Nur Hasina; Iffatul Millah; Faishol Faishol (Jurnal Ilmu Keperawatan Jiwa, 2021)
The COVID-19 pandemic has a major impact, especially on adolescents. This pandemic demands new habits of social distance, home quarantine, learning from home, limiting teenagers from playing and going out of the house with peers. This makes adolescents feel depressed until they experience mental disorders in the form of anxiety. Anxiety that occurs in adolescents can be overcome with music therapy. Music therapy is a therapy that does not have an adverse effect on adolescents and can reduce anxiety levels by increasing endorphins. This type of research is Quasy experimental pre test post test with control group with the sampling technique with purposive sampling. Music therapy was given for 6 days with a duration of 20-30 minutes. The type of music given is in accordance with the music that the respondent likes. Media providing music therapy with mp4. The level of anxiety in this study was measured using the DASS 42 questionnaire with a reliability of r = 0.82 and a validity test with a Cronbach alpha result of 0.85. The results of the paired t-test showed that the value of p = 0.000 in the intervention group with a mean before the intervention was 12.5 (moderate anxiety) and after being given the intervention in the form of music therapy the mean decreased to 5.5 (normal anxiety) and obtained a value of p = 0.000 and in the control group with a mean 12.3 (moderate anxiety) and after getting the mean 15.05 (severe anxiety). Music therapy given to adolescents has benefits in reducing anxiety so that it can be recommended in providing nursing care.